RASA TAKUT DALAM FILM ANIMASI 2 DIMENSI "FEARS" KARYA NATA METLUKHLUKH) - Moch. Yordan Rismarinandyo; Ranesti Damarsuri (SENDIKRAF Jurnal Pendidikan Seni dan Industri Kreatif, 2023)
“Fears” is a graduation film made by Nata Metlukh at Vancouver Film School in 2015. Nata’s first twodimensional animation film got numerous awards at various film festivals. Without dialogs, the film putsforward the strength of how visualization in the form of animation and music represents the feelings of fearin different forms and conditions as the message of the animator. Analysis of “Fears” aims at (1) describingthe plot of the story through the visualization of animation, and (2) exploring the forms and meanings of thefeelings of fear through the interpretation of the visualization of the plot of the story. Fifteen selectedanimation visualizations of black creatures with white eyes --signifying feelings of fear and alwaysshadowing the main animation character and others—were analyzed. The result of the analysis demonstratesthat feelings of fear may be understood by the owners as the entity disturbing, hindering, and limiting theirthoughts and actions; but on the other side, feelings of fear are also understood in a constructive sense whichfacilitates people to be always alert and cautious.